Porceedings: 2nd International Conference on Bridging Innovations in Pharma. Med. & Bio Sciences - 2, Innopharm (International Journal of Pharmacy and Pharmaceutical Sciences, 2017)
Innopharm 2Â is being organized by Paramita Health Care Society in association with Innovare Academics Sciences at M.P. Council of Science & Technology*, Vigyan Bhawan, Nehru Nagar, Bhopal MP, India from Feb 11-12, 2017. (About MPCST) Innopharm is an effort to bring innovations in health, pharmaceutical and allied field at a common platform to enable scientists benefit from innovations of interdisciplinary nature directed towards a common goal: efficient therapeutics. Innopharm1 witnessed novel frontiers in health and pharmaceutical sciences whereby renowned scientists, academicians and industrialists presented their findings/innovations at an international platform with scientists, researchers and academicians from around the globe. In pursuit of promoting and exploring innovations at an international venue Innopharm 2 is yet another step towards discovering and bridging innovations in the pharmaceutical, medical and life sciences towards efficient and safe therapeutics.